2018
DOI: 10.1007/s12520-018-0678-7
|View full text |Cite
|
Sign up to set email alerts
|

Anthropic resource exploitation and use of the territory at the onset of social complexity in the Neolithic-Chalcolithic Western Pyrenees: a multi-isotope approach

Abstract: Carbon (δ 13 C) and nitrogen (δ 15 N) stable isotope analyses from bone collagen provide information about the dietary protein input, while strontium isotopes (87 Sr/ 86 Sr) from tooth enamel give us data about provenance and potential territorial mobility of past populations. To date, isotopic results on the prehistory of the Western Pyrenees are scarce. In this article, we report human and faunal values of the mentioned isotopes from the Early-Middle Neolithic site of Fuente Hoz (Anuntzeta) and the Late Neol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Movement of people during Chalcolithic in the northcentral Spain has been suggested by several authors (Jones et al 2019;Sarasketa-Gartzia et al 2018). At these sites, locals and non-locals were buried together and shared a similar diet (Sarasketa-Gartzia et al 2018), although some of them also showed different dietary intakes (Jones et al 2019).…”
Section: Migrationsmentioning
confidence: 89%
See 4 more Smart Citations
“…Movement of people during Chalcolithic in the northcentral Spain has been suggested by several authors (Jones et al 2019;Sarasketa-Gartzia et al 2018). At these sites, locals and non-locals were buried together and shared a similar diet (Sarasketa-Gartzia et al 2018), although some of them also showed different dietary intakes (Jones et al 2019).…”
Section: Migrationsmentioning
confidence: 89%
“…The dietary information provided by this study is an excellent example of the power of integrating a large, comprehensive dataset. They report a relatively homogeneous diet based on C 3 plants with some contribution of animal protein during the Neolithic, a dietary profile that has also been detected for early farming communities at north-central, north-eastern and south-central Spain (Díaz-Zorita Bonilla et al 2019;Jones et al 2019;Sarasketa-Gartzia et al 2018;Villalba-Mouco et al 2018). Bonilla et al 2019).…”
Section: Comprehending Consumption During Prehistorymentioning
confidence: 89%
See 3 more Smart Citations